2017
DOI: 10.1063/1.4994627
|View full text |Cite
|
Sign up to set email alerts
|

Initial leakage current paths in the vertical-type GaN-on-GaN Schottky barrier diodes

Abstract: Electrical characteristics of leakage current paths in vertical-type n-GaN Schottky barrier diodes (SBDs) on free-standing GaN substrates are investigated by using photon emission microscopy (PEM). The PEM mapping shows that the initial failure of the SBD devices at low voltages is due to the leakage current paths from polygonal pits in the GaN epilayers. It is observed that these polygonal pits originate from carbon impurity accumulation to the dislocations with a screw-type component by microstructure analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 19 publications
1
47
0
Order By: Relevance
“…[2] Its control is crucial for layers with low doping levels and nonuniform incorporation of carbon can reduce the breakdown voltage of electronic devices dramatically. [3][4][5][6] Carbon is suspicious to be related to current collapse and dispersion in transistors when used intentionally in highly resistive buffer layers. [7,8] Thus, the electronic properties of carbon in GaN remain of high interest.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Its control is crucial for layers with low doping levels and nonuniform incorporation of carbon can reduce the breakdown voltage of electronic devices dramatically. [3][4][5][6] Carbon is suspicious to be related to current collapse and dispersion in transistors when used intentionally in highly resistive buffer layers. [7,8] Thus, the electronic properties of carbon in GaN remain of high interest.…”
Section: Introductionmentioning
confidence: 99%
“…Schottky contact made on surface modified GaN showed much better reverse leakage characteristics than unmodified GaN [15]. Sang et al performed detailed analysis on leakage path by photon emission microscopy (PEM), and found the leakage current occurred at polygonal pits, where carbon impurity accumulated and acted as trap in carrier tunneling [16]. The result aligned with the Cao et al's finding that low carbon concentration was necessary to achieve high Schottky contact quality, by an experiment correlating contact performance with carbon doping level [17].…”
Section: Metal Schottky Contacts To Ganmentioning
confidence: 99%
“…Simulation was performed by Baik et al to find the optimized FP structure [45]. A minimum metal overlay extent of 5 μm and a minimum dielectric layer thickness of 0.3 μm for SiNx was needed to avoid dielectric breakdown at the FP on GaN cap layer with an unintentional n doping level of 5 Â 10 16 lead to an optimum dielectric layer thickness; Optimum dielectric layer thickness is related with dielectric permittivity [47]. In summary, both simulation and experiment results demonstrated that addition device structures such as dielectric passivation layer, FRM and FP, can contribute to better GaN SBD performance.…”
Section: Sbd Device Fabrication and Device Structure Optimizationmentioning
confidence: 99%
“…TDs are classified into three types: threading edge dislocations (TEDs), threading screw dislocations (TSDs), and threading mixed dislocations (TMDs), which, propagating in the c ‐axis direction, have Burgers vectors of b = a/3false⟨112false¯0false⟩, c[0001], and c[0001]+a/3false⟨112false¯0false⟩, respectively. Because different types of TDs induce different device behaviors and characteristics, identification and analysis of TDs in GaN crystals is an important research undertaking.…”
Section: Introductionmentioning
confidence: 99%